2x-16+5x=3x-7

Simple and best practice solution for 2x-16+5x=3x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-16+5x=3x-7 equation:


Simplifying
2x + -16 + 5x = 3x + -7

Reorder the terms:
-16 + 2x + 5x = 3x + -7

Combine like terms: 2x + 5x = 7x
-16 + 7x = 3x + -7

Reorder the terms:
-16 + 7x = -7 + 3x

Solving
-16 + 7x = -7 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-16 + 7x + -3x = -7 + 3x + -3x

Combine like terms: 7x + -3x = 4x
-16 + 4x = -7 + 3x + -3x

Combine like terms: 3x + -3x = 0
-16 + 4x = -7 + 0
-16 + 4x = -7

Add '16' to each side of the equation.
-16 + 16 + 4x = -7 + 16

Combine like terms: -16 + 16 = 0
0 + 4x = -7 + 16
4x = -7 + 16

Combine like terms: -7 + 16 = 9
4x = 9

Divide each side by '4'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| 4/5×116 | | 6x^(2/3) | | g-196=-5g-4 | | =x^3+2x^2+4x+8 | | x-40+3x=56 | | 2.5=((x-2000)/2000)/-.30) | | A=10-2b | | 10x-2.25=7x | | 28x^2+186x+96=0 | | (6x)^2/3 | | -7-g=-49 | | -9e+8=e+448 | | 3(x*x)-32=16 | | -37+4x=7x+26 | | n/25=6 | | x^2+2(2k+5)x-(13k+4)=0 | | 7x-7-4x=31 | | X-8y+12=0 | | D+(-22)=(-44) | | 2x-6(x-12)=28 | | 12a/3=8 | | 4c+12=7c+9.21 | | 5/13=c-3/8 | | 80=5/9(F-32) | | 3x+1=ln(13) | | -28x^2-186x-96=0 | | ln(x)=7.2 | | 3t/4=18 | | 10-2h=7a | | -4(-8+7x)=-52 | | 45-x/4+45-x/4+115=180 | | 5m+21=180 |

Equations solver categories